1984
DOI: 10.1111/j.1600-0536.1984.tb01013.x
|View full text |Cite
|
Sign up to set email alerts
|

Contact stomatitis and dermatitis to nickel and palladium

Abstract: 17 subjects were tested epicutaneously with 22 materials, including Ni, Pd, Cr and Co. 5 subjects with a positive allergic skin reaction to Ni were tested with a pure metallic nickel plate 3 X 5 mm, which was attached to the buccal side of one lower premolar. These 5 subjects all developed local allergic contact stomatitis on the mucosa of the cheek adjacent to the metal plate. This was confirmed histologically. The same oral test with pure metallic palladium gave no reaction in subjects with a positive patch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

1992
1992
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(21 citation statements)
references
References 4 publications
1
18
0
2
Order By: Relevance
“…Palladium allergy seems to occur in patients who are also sensitive to nickel (van Ketel and Niebber, 1981;Nakayama, 1982;van Loon et al, 1984van Loon et al, , 1986Stenman and Bergman, 1989;Augthun et al, 1990), but not consistently (Castelain and Castelain, 1987). All casting alloys, except unalloyed titanium, seem to have a potential for eliciting adverse reactions in individual, hypersensitive patients.…”
Section: Reactions To Specific Alloy Systemsmentioning
confidence: 92%
“…Palladium allergy seems to occur in patients who are also sensitive to nickel (van Ketel and Niebber, 1981;Nakayama, 1982;van Loon et al, 1984van Loon et al, , 1986Stenman and Bergman, 1989;Augthun et al, 1990), but not consistently (Castelain and Castelain, 1987). All casting alloys, except unalloyed titanium, seem to have a potential for eliciting adverse reactions in individual, hypersensitive patients.…”
Section: Reactions To Specific Alloy Systemsmentioning
confidence: 92%
“…Even though nickel and other metals used in dentistry have been known to cause oral lichenoid reactions (3), nickel sensitivity is more commonly associated with a generalized skin eruption including urticaria and eczema (4). Contact cheilitis and stomatitis have been reported from nickel (5, 6). However, the occurrence of angular cheilitis following contact sensitivity to nickel in braces has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Limitations of these studies included a lack of knowledge of the composition of the alloy used, sketchy patient histories and uncontrolled conditions or confounding variables. In one interesting study, individuals with Ni and Pd allergy were not allergic to pure Pd metal placed intraorally [49]; this result has been attributed to intraoral corrosion resistance to Pd [1]. Yet, other studies suggest that some Pd-based alloys gradually experience intraoral corrosion of base metal elements, leading to Pd enrichment at the alloy surface and more Pd release over time because of the enrichment [34].…”
Section: Allergy To Pd or Pd Alloysmentioning
confidence: 98%
“…Controversy persists and, to date, no prospective, randomized, appropriately controlled studies have been performed to establish the prevalence of allergic responses to Pd dental alloys. However, several reports have concluded that even in patients with documented Pd allergy, the risk of allergic reaction to Pd alloy is relatively low because of the low corrosion rate of Pd from these alloys [1,42,[49][50][51].…”
Section: Allergy To Pd or Pd Alloysmentioning
confidence: 99%
See 1 more Smart Citation